2021
DOI: 10.5114/ppn.2021.110796
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation as a diagnostic and therapeutic tool in cerebral palsy

Abstract: Purpose: Cerebral palsy (CP) is one of the leading causes of child disability, which profoundly affects the lives of whole families and contributes to the burden of health care. Despite the extensive rehabilitative, surgical and other therapeutic efforts of an array of specialists, a significant proportion of patients remain severely disabled. Transcranial magnetic stimulation (TMS) is a non-invasive diagnostic tool in various diseases of the cerebral cortex and cortico-spinal tract (CST). Repetitive TMS (rTMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 101 publications
0
5
0
2
Order By: Relevance
“…Analyzing the relationships between the control parameters and key biomechanical indicators and achieving standardized comparisons between different control strategies may better guide the future technological development of exoskeleton robot-assisted walking rehabilitation. Recent clinical trials have also revealed that treatment methods developed in neurorehabilitation have been widely studied in CP research, such as transcranial magnetic stimulation ( 48 ), virtual reality technology ( 48 ), whole-body vibration ( 49 ), wearable exoskeletons, and stem cell transplantation ( 45 , 50 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the relationships between the control parameters and key biomechanical indicators and achieving standardized comparisons between different control strategies may better guide the future technological development of exoskeleton robot-assisted walking rehabilitation. Recent clinical trials have also revealed that treatment methods developed in neurorehabilitation have been widely studied in CP research, such as transcranial magnetic stimulation ( 48 ), virtual reality technology ( 48 ), whole-body vibration ( 49 ), wearable exoskeletons, and stem cell transplantation ( 45 , 50 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the effects of magnetic fields on the brain is especially important since magnetic stimulations are already a well-known and well-used method for non-invasive brain stimulation used as both diagnostic and therapeutic tools 20 22 . Since magnetic stimulations can modulate various brain functions, they also have the potential to be used as a treatment for numerous neuropsychiatric diseases 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the effects of magnetic fields on the brain is especially important since magnetic stimulations are already a well-known and well-used method for non-invasive brain stimulation used as both diagnostic and therapeutic tools [20][21][22] . Since magnetic stimulations can modulate various brain functions, they also have the potential to be used as a treatment for numerous neuropsychiatric diseases 23,24 .…”
Section: Introductionmentioning
confidence: 99%